PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI INDUSTRI RUMAHAN BATIK BAHAR BUANA DALAM UPAYA MENINGKATKAN KESEJAHTERAN MASYARAKAT DESA - Syamsul Arifin (AT TAMKIN : Jurnal Pengembangan Masyarakat Islam dan Perubahan Sosial, 2024)
The formation of economic empowerment can help the community get positive activities as well as make the community more creative and benefit by participating in batik making activities, the benefits obtained are also not only in economic terms but gain knowledge about how to make batik properly and well. This research method uses a type of qualitative descriptive research., in this study the author looks for data, researches, studies, and makes direct observations to the location of the research site. The data sources used in this study are primary data and secondary data. Data analysis of this research was carried out in three stages, namely data reduction, data presentation and conclusions. The results showed that; 1). Awareness stage, this stage is the most difficult stage to do, because this stage is the stage of forming behavior towards conscious and caring behavior so that someone feels the need to increase their self-capacity. 2). Transformation stage, this stage is a stage where people are given abilities in the form of insight, knowledge and skills so that they are open to insight and creativity. 3). Stage of intellectual enhancement. The benefits obtained after joining the Bahar Buana batik cottage industry. 1). Social benefits 2). Economic benefits. 3). Benefit skills and knowledge.